Adherence to Mediterranean diet and risk of developing diabetes: prospective cohort study. Issue 7657 (29th May 2008) - Martínez-González, M Á; Fuente-Arrillaga, C de la; Nunez-Cordoba, J M; Basterra-Gortari, F J; Beunza, J J; Vazquez, Z; Benito, S; Tortosa, A; Bes-Rastrollo, M
Abstract : Objective To assess the relation between adherence to a Mediterranean diet and the incidence of diabetes among initially healthy participants. Design Prospective cohort study with estimates of relative risk adjusted for sex, age, years of university education, total energy intake, body mass index, physical activity, sedentary habits, smoking, family history of diabetes, and personal history of hypertension. Setting Spanish university department. Participants 13 380 Spanish university graduates without diabetes at baseline followed up for a median of 4.4 years. Main outcome measures Dietary habits assessed at baseline with a validated 136 item food frequency questionnaire and scored on a nine point index. New cases of diabetes confirmed through medical reports and an additional detailed questionnaire posted to those who self reported a new diagnosis of diabetes by a doctor during follow-up. Confirmed cases of type 2 diabetes. Results Participants who adhered closely to a Mediterranean diet had a lower risk of diabetes. The incidence rate ratios adjusted for sex and age were 0.41 (95% confidence interval 0.19 to 0.87) for those with moderate adherence (score 3-6) and 0.17 (0.04 to 0.75) for those with the highest adherence (score 7-9) compared with those with low adherence (score <3). In the fully adjusted analyses the results were similar. A two point increase in the score was associated with a 35% relative reduction in the risk of diabetes (incidence rate ratio 0.65, 0.44 to 0.95), with a significant inverse linear trend (P=0.04) in the multivariate analysis. Conclusion Adherence to a Mediterranean diet is associated with a reduced risk of diabetes.